PENGARUH PENGGUNAAN VIDEO ANIMASI BERBANTUAN APLIKASI PLOTAGON TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V MI NURUL ISLAM PONTIANAK - Azizah, Ria Dhatul; setyaningrum, saumi; Habaridota, Maha Lastasa Buju Basafpipana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The purpose of this study was to reveal: (1) Learning outcomes before using animated videos assisted by plotagon applications; (2) Learning outcomes after using animated videos assisted by plotagon applications; (3) Whether or not there is an influence on the use of animated videos assisted by the plotagon application on the learning outcomes of students of animal and human organs of motion in class V of Madrasah Ibtidaiyah Nurul Islam Pontianak for the 2021/2022. This research uses a quantitative approach with a pretest postest one group design experiment research design. Data collection techniques are tests, documentation and observations with the tool in the form of a test sheet with 30 multiple-choice questions, a cellphone camera and an observation sheet. Data analysis using instrument analysis and influence analysis. Based on the results of the research and discussion carried out, the researchers concluded that: (1) The learning outcomes of students before using animated video media assisted by plotagon applications averaged 53.47. (2) Application of animated video media assisted by plotagon application with a percentage result of 100%. (3) Student learning outcomes after using plotagon application-assisted animated videos averaged 92.86. (4) There was a significant influence on using plotagon application-assisted animated video with Ho rejected (H? accepted)